Analysis of Parenting with The Risk of Attention Deficit Hyperactivity Disorder (ADHD) in Preschool Children at Kuntum Mawar Kindergarten, West Pamulang - Ardi, Ni Bodro; Rahmi, Junaida; Andriati, Riris; Khairunnisa, Firyal (HealthCare Nursing Journal, 2025)
Parenting refers to how parents guide and educate their children, either directly or indirectly, as part of their responsibility. ADHD (Attention Deficit Hyperactivity Disorder) is a psychiatric condition characterized by difficulty focusing, excessive attention shifts, and hyperactivity. This disorder affects children's learning abilities and daily functioning, with a prevalence of 5-8%, primarily in boys. ADHD rates vary globally, ranging from 2-20%, with 14.5% in the United States, 22.5% in Colombia, 20% in Ukraine, and 26.4% in Indonesia, according to 2007 data from the National Statistics Agency. This study aimed to explore the connection between parenting styles and the risk of ADHD in preschool children at TK Kuntum Mawar, Pamulang Barat. Using a quantitative, cross-sectional design, data were gathered through questionnaires from 64 parents of children aged 5-6 years at TK B Kuntum Mawar. Statistical analysis using the Spearman rank test revealed a significant relationship between parenting styles and the risk of ADHD (p-value = 0.014 <α 0.05). The findings suggest that parenting styles influence the likelihood of ADHD in preschoolers. Parents are encouraged to adopt effective parenting approaches to reduce the risk of ADHD in young children.